Experience involving technology transfer, capacity building, and information exchange for the International Treaty on Plant Genetic Resources for Agriculture - McInerney TF (2014)
Technology transfer, capacity building, and information exchange are important contributors to the accomplishment of the aims of the International Treaty on Plant Genetic Resources for Agriculture (ITPGRA). These matters have been prioritized as approaches to non-monetary benefit sharing in the treaty itself as well as in subsequent decisions by the parties. This report examines practices and experiences among other multilateral treaties for technology transfer, capacity building, and information exchange to identify lessons and provide recommendations on how best to achieve these objectives for the ITPGRA. Effort has been made to identify empirically-grounded evidence of what has or has not worked for other treaties, rather than aiming for a comprehensive but merely general survey of treaties that engage in such activities. The lessons identified will be analyzed in light of the priorities and activities undertaken within the Treaty, particularly through the two rounds of funding under the Benefit Sharing Fund (BSF).